PENETAPAN KADAR MINERAL KALSIUM DAN MAGNESIUM PADA LABU SIAM (Sechium edule (Jacq.) Swartz) MENGGUNAKAN METODE SPEKTROFOTOMETRI SERAPAN ATOM - Daulay, Anny Sartika; Ridwanto, Ridwanto; Rizki, Rahmad (Jurnal Farmanesia, 2020)
Siamese pumpkin (Sechium edule (Jacq.) Swartz) is a plant originating from the cucurbitaceae tribe. This plant is a vegetable that grows in the subtropics that is used as food and at the same time used in medicine. Chayote contains secondary metabolites, minerals, and vitamins. The minerals contained in chayote include potassium, calcium, magnesium, sodium, phosphorus, zinc, iron and manganese. The purpose of this study was to determine the mineral content of potassium, calcium, and magnesium from old and young chayote and to determine the difference in mineral content of young and old chayote. The sample was taken by purposive sampling from Jalan Garu 2, Harjosari II Village, Medan Amplas District, North Sumatra. The sample consisted of old chayote and young chayote. Samples were treated with a wet digestion process. The assay was carried out using atomic absorption spectrophotometry with an air-acetylene flame. Quantitative analysis of potassium, calcium and magnesium was carried out at wavelengths of 766.5 nm, 422.7 nm and 285.2 nm, respectively. The results showed that the mineral levels of potassium, calcium, and magnesium in old chayote were (11.5926 -+ 2.2124) mg/100g, (31.1145 -+ 1.8648) mg/100g, (4.0623 -+ 2.6156) mg/100g. The mineral levels of potassium, calcium and magnesium in young chayote were (16.2461 -+ 2.2547) mg/100g, (16.5038 -+ 1.9765) mg/100g, (5.7721 -+ 0.1935), respectively. mg. There is a difference between the mineral content found in old chayote and young chayote with potassium and magnesium levels in old chayote being lower than young chayote and calcium levels in old chayote being higher than young chayote.